Validation of a Model for Improving the Group Cooperation in School Teachers - S. Rohollah Moosavinejad; Hoosein Karimian; S. Mohammad Bagher Jaafari (Iranian Evolutionary Educational Psychology Journal, 2023)
Considering the current changes and conditions, greater attention should be given to promoting the spirit of cooperation among human resources working in schools in order to achieve organizational goals. With this in mind, the present study aimed to validate a model for improving group cooperation among school teachers. The research employed a descriptive-correlational design. The statistical population consisted of managers and teachers in the field of educational sciences in Qom City in 2021. A sample of 129 participants was selected through accessible sampling method and Cochran's formula. Data was collected using a researcher-made questionnaire consisting of 39 statements. To validate the proposed model, structural equation modeling was performed using PLS software. The findings indicated that the tool designed to test the proposed model had adequate validity and reliability. Additionally, the overall fit of the research model was appropriate and approved. The validation of the identified components showed that all paths had a critical value higher than the critical value (1.96) at the 95% confidence level, indicating the significance of the paths, the appropriateness of the structural model, and the confirmation of all the identified components. In conclusion, the proposed model was approved, and the designed questionnaire can be used to measure the spirit of group cooperation among school teachers.